(untitled) (Annals of Medical Research, 2023)
Aim: To investigate the levels of signal peptide-CUB-EGF domain-containing protein (SCUBE 1 and 3) in rheumatoid arthritis (RA). Materials and Methods: Twenty eight RA patients and 28 healthy volunteers were included in the study. SCUBE-1, SCUBE-3, Vascular Endothelial Growth Factor (VEGF), Matrix Metalloproteinase-9 (MMP-9), CD-40L, Interleukin-6 (IL-6) levels, which are important markers in angiogenesis, were measured twice, at baseline and after the treatment. Results: Compared to the healthy group, only MMP-9, one of the angiogenesis markers, was elevated in the patient group (p>0.05). After treatment, a significant decrease was observed in VEGF levels (p<0.05), while SCUBE-1, SCUBE-3, IL-6, CD-40 and MMP-9 levels remained at similar levels (p>0.05). Conclusion: In our study, RA patients responded to treatment with clinical improvements. Although there were differences in the levels of MMP and VEGF, there was no association with the disease in SCUBE.